Audit Committee, Board, and Audit Report Lag - Ahmad Iskandar Rahmansyah; Siti Maria Wardayati; Muhammad Miqdad (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
Effect of corporate governance being the crucial issue in growing process of audit financial statement in order to decrease audit report lag. Some of previous studies stated that correlation between corporate governance and audit report lag is not consistence. That is why, this study used variable control as firm and auditor characteristics in order to find out the effect of audit committee and board characteristics to audit report lag. The variable independent consist of audit committee size, audit committee independent, board size, board independent, and board meeting, meanwhile the variable control consists of firm size, loss, and quality auditor. Sample of this study is 55 firms in BEI around 2017 2018 periods. The annual financial statement data gotten from BEI official, and analyzed by using multiple regression model. The result showed that only board size has significant effect to audit report lag, while audit committee size, audit committee independent, board independent, and board meeting variables have do not have significant effect to audit report lag.